Evaluating the Interactive Effects of Cordyceps Mushroom Powder and Carbadox to Pharmacological Copper and Zinc for Nursery Pigs - J. Richert; M. Thayer; C. Chastain; A. Duttlinger; J. Feldpausch; R. Garcia; B. Richert; J. L. Nelssen (Kansas Agricultural Experiment Station Research Reports, 2019)
The objective of this study was to evaluate the independent and additive effects ofCordycepsmushroom powder (MP) and carbadox to pharmacological levels of copper and zinc in nursery pig diets. Two hundred and ten crossbred weanling pigs (Duroc × (York × Landrace)) average of 19 d of age and 12.8 lb were used in a 33-day growth trial. Pigs were allotted by weight, sex, ancestry, and assigned to body weight (BW) blocks. Within BW blocks, sex ratios were constant in each pen. Pen was the experimental unit, and growth performance was analyzed using BW, average daily gain (ADG), average daily feed intake (ADFI), and feed-to-gain ratio (F:G). There were 7 pigs/pen and 6 pens/treatment. Treatments were: 1) a negative control diet (NC); 2) positive control (PC; carbadox, 50 g/ton); 3) NC+ 300 ppmCordycepsmushroom powder (NC+MP); 4) PC + 300 ppm mushroom powder (PC+MP); 5) supplemental copper sulfate (125 ppm) and zinc oxide (3000 ppm d 0 to 7, 2000 ppm d 7 to 35), CuZn. Dietary treatments were fed in a four-phase feeding program (d 0 to 7, d 7 to 14, d 14 to 21, and d 21 to 33). Pigs fed the PC, PC+MP, and CuZn diets had increased BW (P<0.05), ADG (P<0.05), and ADFI (P<0.10) over those fed the NC at the end of phases 1, 2, and 3, with no main effect of MP treatment. During phase 4, pigs fed MP, PC, and CuZn diets all had increased ADG (P<0.05; 0.95, 1.05, 1.00, 1.11, 1.07 lb/d, diet 1–5, respectively) and ADFI (P<0.05) over the NC fed pigs. Overall, d 0 to 33, pigs fed PC diets and CuZn had increased ADG (P<0.05) and ADFI (P<0.05), with pigs fed MP tending to have increased ADFI (P<0.08) over NC-fed pigs. Plasma TNF-α concentrations at d 14 postweaning showed a trend for a carbadox main effect, as well as a mushroom by carbadox interaction (P<0.10) for plasma TNF-α, with the 300 ppm MP having the numerically highest value, while the combination of carbadox and 300 ppm MP had the lowest concentration of TNF-α. Feeding nursery pigs pharmacological levels of Cu+Zn and carbadox have economical value to increase nursery pig performance, while MP may increase pig ADFI and final BW through potentially complementary modes of action to carbadox.
Keywords: nursery pigs; growth; antibiotic alternatives